A rare heterozygous variant in FGB (Fibrinogen Merivale) causing hypofibrinogenemia in a Swedish family. Issue 7 (October 2020) - Fager Ferrari, Marcus; Leinoe, Eva; Rossing, Maria; Norström, Eva; Zetterberg, Eva
Abstract : N/A: Fibrinogen is essential for normal hemostasis. Congenital fibrinogen disorders (afibrinogenemia, hypofibrinogenemia, dysfibrinogenemia and hypodysfibrinogenemia), caused by pathogenic variants in the genes FGA, FGB and FGG, have the potential of causing bleeding diathesis and/or thrombotic events of variable severity. We describe a case of familial hypofibrinogenemia in a Swedish family. The proband is a 27-year-old woman, with a history of significant bleeding diathesis. She was diagnosed with moderate hypofibrinogenemia (0.8 g/l), and genetic screening identified a rare heterozygous missense variant in FGB (c.854G>A, p.Arg285His) (Fibrinogen Merivale) previously described in a New Zealand European family with symptomatic hypofibrinogenemia. The father, sister and brother of the proband also harbored the FGB variant, segregating with hypofibrinogenemia (0.9–1.2 g/l). The proband showed a more severe bleeding phenotype compared with her other hypofibrinogenemic family members; this was attributed to a concomitant platelet dysfunction, also present in her normofibrinogenemic mother. Abstract : Supplemental Digital Content is available in the text